Pengaruh Eksposur Video Pendek Tiktok terhadap Motivasi Belajar Siswa dalam Pembelajaran Sains - Seftiani, Mustika Ayu; Fitriyah, Fitriyah; Rahmadani, Okta Dewi Tryshita; Astutik, Sri; Meilina, Ike Lusi (U-Teach: Journal Education of Young Physics Teacher, 2025)
The rapid development of digital media, especially the habit of watching short videos on platforms such as TikTok, has had a major impact on the way of learning in the world of education. This situation is a challenge, especially in maintaining and improving students' enthusiasm for learning in science subjects. This study aims to: (1) find out how often students are exposed to TikTok short videos; (2) analyze how such exposure relates to motivation to learn science; and (3) develop flexible science learning strategies to increase learning motivation in the era of high digital content consumption. This study uses a survey method with a descriptive quantitative approach. Data was collected through questionnaires that contained questions about how often students use TikTok, how students view science learning, and students' levels of motivation to learn. It is hoped that the results of this study can illustrate the relationship between the habit of watching short videos and students' learning motivation, so that it can be used as a basis for developing science learning strategies that are more appropriate and relevant to current conditions